Flunixin meglumine tissue residues after intravenous administration in goats - Giles, Claire B.; Ferdous, Farha; Halleran, Jennifer L.; Yeatts, Jim L.; Baynes, Ronald E.; Mzyk, Danielle A. (Frontiers in Veterinary Science, 2024)
The objectives of the present study were to investigate the depletion of flunixin meglumine in various goat tissues including liver, kidney, fat and muscle. Twenty Boer goats were enrolled and administered an intravenous dose (2.2 mg/kg) of flunixin meglumine. Five animals were randomly euthanized at 24-, 48-, 72-, or 96-hours following dosing. All samples were analyzed via ultraperformance liquid chromatography coupled to mass spectrometry. The concentration of flunixin in all tissues declined rapidly, with the highest mean concentrations quantified in kidney (0.137 ± 0.062 µg/g) and liver (0.077 ± 0.029 µg/g) tissues at 24 hours. Since any detection of flunixin residues at slaughter found in goat tissues is considered a violative residue, a conservative withdrawal interval of 17 days was calculated to ensure levels of flunixin fell below the regulatory limits of detection in liver, kidney and muscle tissues.